1984 a novel - Orwell, George (New York, N.Y Signet Classics, 1977)
Portrays life in a future time when a totalitarian government watches over all citizens and directs all activities
1
Keywords: Orwell, George -- 1903-1950 -- Nineteen eighty-four; Science fiction, English; Totalitarianism -- Fiction